Rheumatic and musculoskeletal immune-related adverse events due to immune checkpoint inhibitors: A systematic review of the literature - Cappelli, Laura C. (Arthritis Care Res (Hoboken), 2017)
BACKGROUND: Immune checkpoint inhibitors (ICI) are improving prognosis in advanced stage cancers, but also lead to immune-related adverse events (IRAE). IRAEs targeting many organ systems have been reported, but musculoskeletal and rheumatic IRAE have not been well characterized. We systematically reviewed published literature on musculoskeletal and rheumatic IRAE to better understand prevalence and clinical characteristics. METHODS: Medline and CENTRAL databases were searched for articles reporting rheumatic and musculoskeletal IRAEs secondary to ICI treatment. After screening abstracts and full texts in duplicate, clinical features, prevalence and treatment data were extracted and summarized. RESULTS: 1725 unique abstracts were screened; 231 contained original data and were about ICIs and went to full text screening. Fifty-two of these contained information about musculoskeletal or rheumatic IRAEs or about treatment with ICIs in pre-existing autoimmune disease. Of these, 33 were clinical trials, 3 were observational studies, and 16 were case reports or series. Arthralgia prevalence in clinical trials ranged from 1–43%, and myalgia was reported in 2–20%. Arthritis was reported in 5/33 clinical trials, and vasculitis was reported in only 2. One observational study and 3 case reports described patients with pre-existing autoimmune disease treated with ICIs. Case reports included development of inflammatory arthritis, vasculitis, myositis, and lupus nephritis. CONCLUSIONS: Arthralgia and myalgia have been reported commonly in patients treated with ICIs. The prevalence of rheumatic IRAEs like inflammatory arthritis, vasculitis, and sicca syndrome is less clear from current evidence. There is limited observational and case-level evidence describing ICI use in patients with pre-existing autoimmune disease.